2022
DOI: 10.1002/vrc2.508
|View full text |Cite
|
Sign up to set email alerts
|

Equine papillomavirus type 2‐associated, carcinomatous lesions of the penis and laryngopharynx of an elderly Icelandic horse gelding

Abstract: A 28‐year‐old Icelandic horse gelding was presented with a laryngopharyngeal squamous cell carcinoma. The gelding had been treated for penile carcinoma in situ with a partial phallectomy 2 years earlier. Polymerase chain reaction of tumour DNA and subsequent amplicon sequencing revealed that the equine papillomavirus type 2 E6 oncogene sequences of both lesions were identical. There is strong evidence that equine papillomavirus type 2 is causally associated with genital squamous cell carcinomas and precancerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
1
1
1
Order By: Relevance
“…SCCs are invasive tumours that compromise the health of affected horses. SCCs typically affect elderly horses, as seen in our study (Lale et al., 2023 ; Sykora & Brandt, 2017 ; Van Den Top et al., 2008 ). In our study population, the mean age of horses with SCC of any location was 20 years with most of the horses being warmbloods (38%), followed by Icelandic horses (24%), Welsh ponies (9.5%) and Shetland ponies (9.5%).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…SCCs are invasive tumours that compromise the health of affected horses. SCCs typically affect elderly horses, as seen in our study (Lale et al., 2023 ; Sykora & Brandt, 2017 ; Van Den Top et al., 2008 ). In our study population, the mean age of horses with SCC of any location was 20 years with most of the horses being warmbloods (38%), followed by Icelandic horses (24%), Welsh ponies (9.5%) and Shetland ponies (9.5%).…”
Section: Discussionsupporting
confidence: 77%
“…In humans, oropharyngeal SCCs are most often associated with HPV type 16 (Hibi et al., 2019 ; Zaravinos, 2014 ). In our study, no other concomitant EcPV2‐associated lesions were reported in the same horse, although there have been a few reports of horses showing two separate EcPV2‐associated lesions in different locations (Bogaert et al., 2012 ; Lale et al., 2023 ; Porcellato et al., 2020 ). However, in cases of multifocal manifestation of EcPV2‐associated carcinomatous lesions, it often remains unclear whether this is due to metastatic disease or just coincidental development of the lesions.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation